2016
DOI: 10.4103/2152-7806.187492
|View full text |Cite
|
Sign up to set email alerts
|

Comparative outcome analysis of anterior choroidal artery aneurysms treated with endovascular coiling or surgical clipping

Abstract: Background:Treatment of anterior choroidal artery (AChA) aneurysms with endovascular coiling or surgical clipping may increase the risk of ischemic complications owing to the critical territory supplied by the AChA. We analyzed the surgical results of endovascular coiling and surgical clipping for AChA aneurysms performed in a single institution, as well as the role of indocyanine green-videoangiography (ICG-VAG) and motor-evoked potential (MEP).Methods:We analyzed 50 patients (51 aneurysms; 21 men, 29 women; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 21 publications
2
15
0
Order By: Relevance
“…Aoki et al [2] reported a favorable outcome of 79% in the form of no fresh deficits in a retrospective study of 50 patients in Japan who underwent surgical clipping or coiling for incidental IC PC aneurysms.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Aoki et al [2] reported a favorable outcome of 79% in the form of no fresh deficits in a retrospective study of 50 patients in Japan who underwent surgical clipping or coiling for incidental IC PC aneurysms.…”
Section: Discussionmentioning
confidence: 99%
“…This is a finding observed in all the previously compared studies who confirmed the projection of the aneurysm posteriorly in cases who had postoperative complications. [2162221]…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Anterior choroidal artery (AChoA) aneurysms are rare, accounting for approximately 2–5% of all intracranial aneurysms (Locksley et al, 1966 ; Kim et al, 2009 ; Aoki et al, 2016 ). Compared with clipping, endovascular treatment (EVT) is an established treatment option for intracranial aneurysms with shorter hospital stays and better recovery specially in the elderly people (Sadamasa et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%